Ergonomic redesign of transportation fleet driver seats using anthropometric approaches to minimize musculoskeletal disorders - Andriani, Meri; Hamdani, Hamdani; Aziza, Nanda Saleysia (Jurnal Polimesin, 2025)
The operation of public transportation fleets demands competent drivers to ensure passenger safety and operational reliability. Maintaining an optimal driving posture is a critical factor in supporting driver performance; however, mismatches between seat design and driver anthropometry can result in musculoskeletal disorders (MSDs), reducing driver focus and increasing the risk of traffic accidents. This study aims to determine the ergonomic dimensions of driver seats based on anthropometric data. The methodology integrates anthropometric measurements, percentile analysis, statistical validation, and ergonomic modeling utilizing CATIA software. Key anthropometric dimensions considered include sitting upright height (TDT), chin-to-top-of-head distance (DPK), shoulder width (LB), popliteal-buttock length (PPO), popliteal height (TPO), thigh thickness (TP), and hip width (LP). Data uniformity and adequacy tests confirmed the reliability of the dataset, while normality tests verified that the measurements were normally distributed. Subsequent analysis applied the 50th and 95th percentile values to guide design decisions, ensuring broad user accommodation. Ergonomic modeling was conducted using CATIA software to develop an optimized driver's seat. The resulting design specifications include a seat base height of 92.63 cm, headrest height of 21.7 cm, seat width of 62 cm, seat base length of 46.90 cm, seat height from the floor of 44.00 cm, seat base thickness of 15.07 cm, and seat base width of 38.33 cm. These dimensions are intended to support optimal driver posture, reduce the incidence of MSDs, and enhance overall driving safety and comfort in public transportation fleets.